If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -10y = -13 Solving 9x + -10y = -13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10y' to each side of the equation. 9x + -10y + 10y = -13 + 10y Combine like terms: -10y + 10y = 0 9x + 0 = -13 + 10y 9x = -13 + 10y Divide each side by '9'. x = -1.444444444 + 1.111111111y Simplifying x = -1.444444444 + 1.111111111y
| 1/4(-8g+24)=g | | 5v-4-6=15+4v | | 4x+14=11x-2 | | 2x+63=9 | | ((1/t)-1)/(t-1) | | 7(4n+4)-10= | | -40n-43=3n | | 8n+8(n+7)=-35+3n | | ((x^8y^-4)/(16^(4/3)))^(-1/4) | | Y=-8x^2-10x+3 | | 6X+16=2x-12 | | 142.09=6s+17.47 | | -5x+9=-4x+8-x-3 | | 14/15x=12 | | -14-v=1+2v | | 5v^2-9=81 | | 3(w-7)-3=-5(-4w+6)-5w | | 2-2y=14+4y | | 2m/7=6/21 | | -25+6x=-3(7-2x) | | 4y+9-6y=15-8y | | 5n-7=7(n-1)-2n | | 1790/0.08 | | -16t^2+124t-84=0 | | 10/13x=4 | | 1+6b+4b-4=4b+7b | | 4x^2(x^2+6xy-7y^2)= | | 5(x+2)+x=6(x+3)-4 | | -7+9x=20 | | -17=13+-10n | | X^2-8x-16=81 | | 3c+6-4c=4+2c |